The Effect of Task- Based Learning (TBL) on Students’ Reading Comprehension - Regar, Elisabet Evie Vania Br; Sinaga, Dolli Rotua; Lumbangaol, Reni Rosianna (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research explores the impact of the Task-Based Learning (TBL) approach on students' performance in reading comprehension. The primary aim is to determine how the TBL method influences students' reading comprehension achievements. The study involves a population of 52 students, all students are taken as samples from 2024/2025 X grade students of Private Senior High School of SMA Free Methodist I, Medan, divided into two groups. The experimental group is taught using the TBL approach, while the control group follows a conventional teaching method. Data collection is conducted through objective tests, including pre-tests and post-tests. The reliability of the test was measured at 0.87, categorized as very high. The analysis revealed a t-observed value of 4.000, which exceeds the t-table value, confirming that the hypothesis (Ha) is accepted. This indicates that students taught using the TBL approach achieved higher reading comprehension scores compared to those taught with traditional methods.